The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/01494929.2017.1283382
|View full text |Cite
|
Sign up to set email alerts
|

The Far-Reaching Consequences of Job Insecurity: A Review on Family-Related Outcomes

Abstract: Job insecurity (JI) appears a fairly stable job stressor in working life today and likely to impair employee well-being. This review article presents the key findings of studies examining the effects of perceived JI on family well-being (e.g., marital/parental role quality, work-family conflict). The results, based on 25 published peer-reviewed studies, suggest an association between JI and impaired family well-being. Thus, JI spills over into family life as proposed in the spillover theory of work-family inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(86 citation statements)
references
References 64 publications
(116 reference statements)
8
71
0
7
Order By: Relevance
“…The study investigated potential gender differences with an exploratory perspective (without formulating specific hypotheses) and tested the three above mentioned study hypotheses separately for women and men. Indeed, previous studies found gender differences in crossover and spillover effects involving job insecurity; nevertheless, results seem not to be fully consistent ( Mauno et al, 2017 ). According to Westman (2001) , differences between women and men may be found in several aspects: (1) in the way they react to events happening to the other partner; (2) in the involvement level in family affairs; (3) in demands and expectations traditionally expected.…”
Section: Gender Differencesmentioning
confidence: 79%
See 1 more Smart Citation
“…The study investigated potential gender differences with an exploratory perspective (without formulating specific hypotheses) and tested the three above mentioned study hypotheses separately for women and men. Indeed, previous studies found gender differences in crossover and spillover effects involving job insecurity; nevertheless, results seem not to be fully consistent ( Mauno et al, 2017 ). According to Westman (2001) , differences between women and men may be found in several aspects: (1) in the way they react to events happening to the other partner; (2) in the involvement level in family affairs; (3) in demands and expectations traditionally expected.…”
Section: Gender Differencesmentioning
confidence: 79%
“…In their review, Mauno et al (2017) reported differences between women and men in the consequences of job insecurity on family-related outcomes. For example, Kinnunen and Mauno (1998) showed that job insecurity decreased work–family conflict only for women.…”
Section: Gender Differencesmentioning
confidence: 99%
“…Instead, they may attempt to compensate by resorting to personal (non-work-related) resources. This defensive, self-protective dynamic also consumes energy in the form of worry and stress, thus decreasing resources, creating strain for the employee, and reducing well-being (Vander Elst et al 2012;Mauno, Cheng, and Lim 2017). It also raises the question of which individuals are most strongly affected (Bonoli 2017): A key aspect of why some individuals are more capable of coping with job insecurity is access to certain fundamental resources.…”
Section: Job Insecurity and Well-beingmentioning
confidence: 99%
“…Since there is no evidence of differences of coping with uncertainty between students and professionals, no differences are expected between these groups. However, considering the added uncertainty that can be found in professional contexts and in the labor market, as well as its psychological effects (de Witte, Pienaar, & de Cuyper, 2016;Giunchi, Emanuel, Chambel, & Ghidlieri, 2016;Jesus et al, 2016;Martín-Artiles, Molina, & Carrasquer, 2016;Mauno, Cheng, & Lim, 2017;Obschonka & Silbereisen, 2015), it was decided to explore if there could be any differences between these two groups. On the other hand, university and technical/professional courses' students may also feel an added strain of uncertainty, by anticipating the transition to the labor market, which would explain if no differences were found.…”
Section: Introductionmentioning
confidence: 99%